Yedoma sediments with gravel and rock debris inclusions: Characteristics and origin. (28th March 2023) - Vasil'chuk, Yurij K.
Abstract: Yedoma ice complex sediments with large syngenetic ice wedges (IW) are usually observed in outcrops in river valleys on permafrost plains and on sea coasts and lake shores in the north of Siberia, Alaska, and Canada. Less frequently, they occur in mountainous and foothill regions of East Siberia, for example, in the Upper Kolyma Upland and in river valleys of the Eastern Sayan Range and the Anabar Plateau, as well as in Alaska and Yukon. The author's materials on gravelly Yedoma with IWs in the intermountain basins, on mountain slopes, and on sea coasts and lake shores are presented. The obtained data allow a conclusion that gravelly Yedoma has mainly alluvial, lacustrine, and colluvial origins with an insignificant participation of aeolian processes. Occurrence of the late Pleistocene gravelly deposits with large syngenetic IWs confirms a hypothesis of polygenetic origin of Yedoma.